SELECTIVE VIDEO STREAM ENCRYPTION METHODS IN TELECOMMUNICATION SYSTEMS BASED ON HIDDEN BASIC I-FRAMES - Бараннік, В.В.; Комолов, Д.І; Рябуха, Ю.М. (Science-based technologies, 2015)
In this article the selective encryption method of video frames based on a hidden baseline I-frame. The work of this method is based on the processing-frame, taking into account the algorithm MPEG, which is implemented on the basis of the formation of different types of video sequences. The article also presents algorithms and coding and decoding the video stream using this method. A method for estimating the amount of hidden I-frame and its compressed representation without hiding under a group of frames in percentage. The analysis of changes in the volume of the compressed representation of the frame with a hidden base frame relative to the original volume of the compressed-frame depending on the different values ​​of the peak signal / noise ratio for different frame types. The methodological basis for determining the difference between the amount of compressed representations of frames using hide the underlying I-frame and no hidden as a percentage.